Strategi Peningkatan Kapasitas Rumah Tangga Petani Padi Sawah Lebak Menuju Ketahanan Pangan Rumah Tangga (Kasus di Kabupaten Ogan Ilir dan Ogan Komering Ilir, Sumatera Selatan) - Yunita Yunita; Basita Ginting Sugihen; Pang S Asngari; Djoko Susanto; Siti Amanah (Jurnal Penyuluhan, 2012)
To fullfill their household food security, farmers living at lowland areas should have high capacities in improving their productivity and income in order to have food acessibility. The use of lowland areas in South Sumatera have known and have managed by society since along time ago. Some farmers have their own land (owner) and the others don’t have any land property. Nowadays farmers at lowland areas are in difficult conditions because of the climate change impact, bio-physic and socio economic problems. Farmers at lowland areas tend to have the risk at food security. Why the household of lowland farmers still faced with insecurity risk, how the capacity level influenced it, and how the alternative strategy to increase capacity of lowland farmers household, are the problem that undertake in this research. This research used survey design to 200 household of lowland farmers at Ogan Ilir and Ogan Komering Ilir District South Sumatera Province based on landowner status. Data were collected on April-June 2010. Analyzed were performed with descriptive technique and Structural Equations Model (SEM). Conclussion of this research are: (1) food security of lowland farmers are low, the influenced factors is social environment feature, empowering process, capacity of farmers houshold and extension performance; (2) capacity of farmers househould positively influenced the food security of household; (3) the capacity of farmers household increasing may obtain by emendation of empowerment process, strengthen the social environment support, and enhancement of empowerment agriculture extension.Keywords: Farmers household capacities, household food security